Perancangan Media Pembelajaran IPA Berbasis AugmentedReality Menggunakan Assemblr Edu Kelas VIII Di SMP N 1 Sungai Pua - Sari, Salsabila; Musril, Hari Antoni; Jasmienti; Derta, Sarwo (Universitas Islam Balitar, 2024)
This research uses Research and Development (R&D) using Luther Sutopo's version of the Multimedia Development Life Cycle (MDCL). The research process was carried out at SMP Negeri 1 Sungai Pua in order to create augmented reality-based science learning media products for class VIII. Luther stated that there are six stages involved in multimedia development: concept, design, material gathering, assembly, testing, and distribution. The author succeeded in creating augmented reality-based learning materials based on research findings. The media produced in this research is not only intended for students, but teachers can also access and use it. Experts in the field of learning media design also verify the correctness of the development results. Four validators provided results and the average result was 0.84, which is included in the valid category. The practicality score for the three examiners was 0.93, which is classified as very practical, while the effectiveness result of 23 students and one teacher in science subjects was 0.92, which is classified as very effective. This product trial resulted in the conclusion that class VIII of SMP Negeri 1 Sungai Pua could benefit from the results of creating augmented reality-based science learning materials for class VIII using Assemblr Edu.